2013
DOI: 10.1128/mcb.00343-13
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA 329 Suppresses Angiogenesis by Targeting CD146

Abstract: b CD146, an endothelial biomarker, has been shown to be aberrantly upregulated during pathological angiogenesis and functions as a coreceptor for vascular endothelial growth factor receptor 2 (VEGFR-2) to promote disease progression. However, the regulatory mechanisms of CD146 expression during angiogenesis remain unclear. Using a microRNA screening approach, we identified a novel negative regulator of angiogenesis, microRNA 329 (miR-329), that directly targeted CD146 and inhibited CD146-mediated angiogenesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
58
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 49 publications
4
58
0
Order By: Relevance
“…Among the miRs, miR-411 regulates myogenesis by targeting myogenic factors (39), and miR-494 regulates the mitochondrial biogenesis of skeletal muscle by targeting mitochondrial transcription factor A and Forkhead box j3 (40). MiR-329 can inhibit cell proliferation and angiogenesis in vitro by targeting E2F and KDM1A (41,42). We measured the expression of E2F, KDMIA, and other target proteins of the miR-379/miR-544 cluster in neonatal mice and found no apparent change that was consistent with the expression of the transcripts of this cluster (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Among the miRs, miR-411 regulates myogenesis by targeting myogenic factors (39), and miR-494 regulates the mitochondrial biogenesis of skeletal muscle by targeting mitochondrial transcription factor A and Forkhead box j3 (40). MiR-329 can inhibit cell proliferation and angiogenesis in vitro by targeting E2F and KDM1A (41,42). We measured the expression of E2F, KDMIA, and other target proteins of the miR-379/miR-544 cluster in neonatal mice and found no apparent change that was consistent with the expression of the transcripts of this cluster (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown differential expression of miR-362-3p in various tissues including the fetal brain of mice, estrogen receptor-positive breast tumors, gastric cancer, and melanoma as well as downregulation of miR-329 in glioma, neuroblastoma, and the mouse model of Rett syndrome. 20,22,29,[33][34][35][36][37][38] The detailed mechanism, however, that governs the differential expression of the two miRs has not been fully elucidated.…”
mentioning
confidence: 99%
“…CD146 has been identified as an adhesion molecule expressed at the intercellular junction of endothelial cells [15]. More recently, CD146 was found to be involved in endothelial cell activity and angiogenesis [37][38][39]. The membrane glycoprotein CD146 is rarely found in the blood of healthy subjects, while a soluble form of CD146, which is generated probably by extracellular shedding, proteolysis or DNA splicing from damaged endothelium, was confirmed to be increased in the peripheral circulation of patients with tumor [22], inflammatory diseases [20] or CKD [18], suggesting a pivotal role of this soluble biomarker in the pathogenesis of angiogenesis and vascular endothelial alteration.…”
Section: Discussionmentioning
confidence: 99%